Effect Of Foliar Fertilizer Interval And Types Of Planting Media On The Growth Of Dendrobium Hybrid Orchids - Ainii Asyary, Dzakiyyah Qurrotu; Permatasari, Ninda Asfia; Suciaty, Tety (Ann Publisher, 2024)
Orchids are epiphytic plants that only absorb a few nutrients through the roots, so using leaf fertilizers and planting media is one solution to increase the nutrients in orchid plants. This research was conducted in the greenhouse of Situgangga Village, Karyaryamulya Village Kesambi District, Cirebon City, West Java Province in June-September 2024. The experimental design was a completely randomized (CRD) treatment consisting of 9 repeated treatments 3 times. The variables observed were plant height, leaf length, leaf width, leaf thickness, number of leaves, number of roots, stomata density, and chlorophyll content. The results showed that using fern planting media and foliar fertilizer at intervals of 9 days gave good results on plant height, leaf length, and number of leaves.